Restoring responsibility : ethics in government, business, and healthcare - Thompson, Dennis F. (Dennis Frank), 1940- (Cambridge University Press, 2005)
In this important collection of essays Dennis Thompson argues for a more robust conception of responsibility in public life than prevails in contemporary democracies. He suggests that we should stop thinking so much about public ethics in terms of individual vices (such as selfishness or sexual misconduct) and start thinking about it more in terms of institutional vices (such as abuse of power and lack of accountability). Combining theory and practice with many concrete examples and proposals for reform, these essays could be used in courses in applied ethics or political theory and will be read by professionals and graduate students in schools of political science, public policy, law, public health, journalism and business.